The British Commonwealth and the Allied occupation of Japan, 1945-1952 personal encounters and government assessments - Nish, Ian. (Leiden : Global Oriental, 2013)
The Allied Occupation of Japan lasted from 2 September 1945 to 28 April 1952 and ushered in an era of unprecedented change for that country. Although British Commonwealth participation played only small part in that story – involving only some 30,000 troops from the various Commonwealth countries compared with the vast numbers of the United States Eighth Army – it nevertheless prompts a discussion, hitherto largely undocumented, concerning its role and relevance. In The British Commonwealth and the Allied Occupation of Japan , Ian Nish who himself was a member of BCOF presents papers by twenty-three authors, partly biographical, partly academic, on subjects grouped in five themes: Origins of the Allied Occupation, Attitudes on the Occupation, Personal Views, the Commonwealth and Peace Negotiations, and the Commonwealth and the Japanese Treaties.
Preliminary Material / Ian Nish -- Introduction / Ian Nish -- Personal Reminiscences of the Early Months of the Occupation: Yokosuka and Tokyo, September 1945–March 1946 / W.G. Beasley -- MacArthurian Japan: Remembered and Revised / Grant K. Goodman -- Reminiscences of a Misspent Youth: Tokyo, 1946–49 / Hans H. Baerwald -- Australia and the Occupation of Japan / Geoffrey Bolton -- New Zealand and the Occupation of Japan / Gordon Daniels -- Canada and the Occupation of Japan / Hamish Ion -- India and the Occupation of Japan / Ian Nish -- Impressions of a Japanese Historian / Takemae Eiji -- An Australian’s Experiences / T.B. Millar -- Some Royal Navy Reflections / Walter Miller -- RAF Experiences / Hugh Cortazzi -- A British Army Perspective / Ian Nish -- A Historian and the International Military Tribunal for the Far East (IMTFE) / R. John Pritchard -- Commonwealth Cooperation and Rivalry / Kibata Yoichi -- Truman, Attlee and the Korean War Crisis / Roger Dingman -- The Dulles-Yoshida Talks, 1950–1951 / Hosoya Chihiro -- Yoshida Shigeru and the Political Parties’ Difficulties over the Question of the San Francisco Peace Treaty / Tozawa Kenji -- Britain’s Labour Government and the Japanese Peace / Peter Lowe -- Hong Kong and San Francisco: Anglo-American Debate on East Asia and the Japanese Peace Settlements / Roger Buckley -- Britain and Japan, 1951: San Francisco and Tokyo / Hugh Cortazzi -- San Francisco Treaty-Making and Its Implications for New Zealand / Ann Trotter -- Australia, the Japanese Peace Treaty and the ANZUS Pact / Neville Meaney -- Appendix: John Northcott’s Notice on Fraternization / Ian Nish -- Index / Ian Nish.
Description based upon print version of record.
Includes bibliographical references and index.
English
Keywords: British Commonwealth Occupation Force; History -- Japan; Japan -- History -- Allied occupation, 1945-1952.; Commonwealth countries -- Foreign relations -- Japan; Japan -- Foreign relations -- Commonwealth countries; Great Britain -- Foreign relations -- Japan; Japan -- Foreign relations -- Great Britain